Tetrakis[diamminesilver(I)] bis(2-hydroxy-5-methylbenzene-1,3-disulfonate) monohydrate - Zhang, Li-Wei; Gao, S.; Ng, S.W. (International Union of Crystallography, 2011)
In the crystal structure of the title salt, [Ag(NH(3))(2)](4)-(C(7)H(6)O(7)S(2))(2)center dot H(2)O, the four independent Ag(I) complex cations all lie on special positions of m site symmetry, as do the two independent 2-hydroxy-5-methylbenzene-1,3-disulfonate anions. The Ag(I) cations exist in an almost linear coordination geometry [N-Ag-N = 175.2 (2), 178.08 (16), 175.8 (2) and 178.20 (19)degrees]. The water molecule is disordered about a mirror plane. Two independent complex cations are linked by an Ag center dot center dot center dot Ag interaction of 3.3151 (1) angstrom, furnishing a linear [Ag(NH(3))(2)](n) polycationic chain running along b. The free complex cations, polycationic chain and 2-hydroxy-5-methylbenzene-1,3-disulfonate anions interact via N-H center dot center dot center dot O and O-H center dot center dot center dot O hydrogen bonds, forming a three-dimensional network.